Light-Driven, Quantum Dot-Mediated Regeneration of FMN To Drive Reduction of Ketoisophorone by Old Yellow Enzyme (2012)
We report the full reduction of the biological cofactor FMN with visible light using CdSe quantum dots and methylviologen as an electron relay. In turn, these reducing equivalents can drive the stereospecific reduction of ketoisophorone by an old yellow enzyme homologue from Bacillus subtilis (YqjM). The experiments demonstrate the current capabilities and limitations of quantum dots as part of a cofactor regeneration system and pave the road for future studies aimed at new and improved in situ light-driven cofactor regeneration strategies.